Audit Sistem Informasi Manajemen Aset Berdasarkan Perspektif Proses Bisnis Internal Balanced Scorecard Dan Standar COBIT 4.1 (Studi Kasus: PT. Pertamina (Persero) - Dewi, Eva Rusdiana; Tanuwijaya, Haryanto; Mastan, Ignatius Adrian (Jurnal JSIKA, 2012)
Information Technology Marketing & Trading (IT M & T) 3rd regional area of PT. Pertamina (Persero) handling multiple processes that one of them is the asset management. Activities of the process includes analysis of hardware requirements of each business unit as East Java, Bali and West Nusa, and do hire and purchases, until the distribution of hardware to each business unit. In managing the process, used in some application such as SAP and the other application which development by them, such as asset management application, helpdesk, and application of OpManager, which was mainly the implementation of asset management application have not been audited to ensure IT alignment with business goal. To measure the alignment between business processes, applications, and the company´s business strategy is necessary to do an audit information system with standard COBIT 4.1. Because the calculation of COBIT  can represent the maturity level of a company. While the asset management process in PT. Pertamina(Persero) is based on company policy with the intention of improving the quality of existing processes, the audit focused on internal business process perspective of Balanced Scorecard. The result of this audit declared that the asset management process maturity level is at its managed and measured to indicate that the organization has had performance indicators, monitor and improve processes and have auxiliary devices for process control. Keywords: asset management, COBIT, maturity level, the Balanced Scorecard.